2019
DOI: 10.1016/j.jad.2018.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism and extraversion mediate the relationship between having a sibling with developmental disabilities and anxiety and depression symptoms

Abstract: Background Children growing up with a sibling with disabilities report higher levels of depression and anxiety symptoms as adults. Here, we examined whether personality characteristics also play a part in mediating this relationship. Method We tested for differences in personality traits between 132 individuals who have a sibling with developmental disabilities and 132 closely matched comparisons. Results Differences in Big Five factors of personality were demonstrated across the disability groups and between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 64 publications
1
13
0
5
Order By: Relevance
“…First, abundant evidence links personality with negative emotions. Relationships between personality and negative emotions can theoretically be organized in several ways (Akiskal et al 1983; Murray & O'Neill 2019; Segerstrom & Smith 2019). Our study also found that introversion–extroversion and neuroticism can predict depression directly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, abundant evidence links personality with negative emotions. Relationships between personality and negative emotions can theoretically be organized in several ways (Akiskal et al 1983; Murray & O'Neill 2019; Segerstrom & Smith 2019). Our study also found that introversion–extroversion and neuroticism can predict depression directly.…”
Section: Discussionmentioning
confidence: 99%
“…Extraversion and neuroticism also contribute mediating effects towards the development of depression and anxiety. Specifically, neuroticism has been suggested to be a strong mediator of anxiety (Grav et al 2012; Murray & O'Neill 2019). Moreover, the presence of psychoticism predicted motivational–somatic symptoms of depression (García‐Torres & Alós 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, relationships with brothers and sisters contribute to the development of their personality traits and the development of coping strategies. In particular, a positive relationship with brothers and sisters, characterized by low conflict and high levels of closeness and affection, seems to predict personality traits such as extraversion and openness [4] and more adaptive coping strategies [5,10,14,18]. However, as far as we are aware, this was the first study to test the moderating role of the quality of the relationship with brothers and sisters between personality traits and coping strategies in individuals raised with typical development siblings and siblings with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, growing up with an S-ID can have an effect on the psychological growth of individuals and could exacerbate certain personality traits. Recent research [4] has shown that adults who have grown up with an S-ID tend to have higher levels of (N) and (O) and lower levels of (E), and these traits may pose a risk of distress and a reduction in the psychological wellbeing of adult S-TDs. Some evidence, derived from typical development dyads, supports an association between personality traits and the quality of the relationship with their brothers or sisters and TD in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, extroversion and neuroticism cooperate as a mediating effect in the development of depression and anxiety. Specifically, research evidence [40,41] suggests that neuroticism is a potent mediator of anxiety.…”
Section: Introductionmentioning
confidence: 99%